(untitled) (Eurasian Journal of Ecology, 2025)
This article reports and analyzes the results of completed and ongoing studies on hematologic data to identify the association between patient deterioration and serum ferritin levels in COVID-19 hospitalized patients. The infectious agent, SARS-Cov-2 virus, is known to be highly virulent. Therefore, WHO has declared the COVID-19 outbreak as a pandemic. Elevated ferritin levels have been found in patients with severe coronavirus infection. Hence, the aim of this study was to determine the relationship of ferritin with critical condition and mortality in COVID-19 patients. A total of 32 papers that collected hematologic data from 9459-hospitalized patients were included in the study process. Thirteen studies were taken to analyze the relationship of ferritin with mortality and critical status, in which data from 6306 infected individuals were reviewed. Ferritin levels were significantly elevated in critically ill patients compared with ferritin levels in patients with less severe disease. Fatal infected patients had high ferritin levels compared with those of non-fatal patients. Patients with one or more comorbidities, including diabetes, thrombotic complications, and cancer, had higher ferritin levels than patients without comorbidities. And also liver injury and the development of acute respiratory distress syndrome (ARDS) were associated with high ferritin levels, and its levels were associated with patients being admitted to the intensive care unit (ICU) and needing ventilator support. Hyperferritinemia is associated with an unfavorable prognosis and may be a marker of deterioration in COVID-19 patients. Keywords: COVID-19, coronavirus, ferritin, critical cases, fatalities